Effectiveness of renewable energy solar cell learning media in vocational education for electrical engineering - Agus Irfan; Lukman Nulhakim; Suhendar Suhendar; Siswo Wardoyo; Mia Widyaningsih (Universitas Sarjanawiyata Tamansiswa, 2025)
Vocational education demands continuous innovation in instructional media to enhance students’ comprehension of increasingly complex technical concepts. In response to the global shift toward sustainable energy solutions, this study aims to evaluate the effectiveness of solar panel trainers as hands-on, technology-based learning tools in the teaching of electrical installation engineering. Utilizing a quasi-experimental design with pre-test and post-test control groups, the research was conducted at a vocational high school and involved two student groups: one using conventional learning methods and another using solar panel trainers. Data were collected through structured tests assessing both theoretical understanding and practical skills. The results indicate a statistically significant improvement in the experimental group’s performance, particularly in understanding the principles of renewable energy and applying them in electrical system installations. These findings highlight the pedagogical benefits of integrating renewable energy technologies into vocational curricula. The study suggests that using practical, real-world tools like solar panel trainers not only enhances learning outcomes but also equips students with relevant competencies for sustainability-driven industries.